The effect of motor vehicle tax and motor vehicle title transfer fee on regional original revenue: a study on local Governments in the special region of Yogyakarta for the 2019–2024 period - Kris Brantas Abiprayu; Muhammad Fais Hakim Rasyid (PHINISI, 2026)
This study aims to analyze the influence of Motor Vehicle Tax (PKB) and Motor Vehicle Name Return Duty (BBNKB) on Regional Original Revenue (PAD) in the Regional Government of the Special Region of Yogyakarta during the 2019-2024 period. The method used is a quantitative approach with multiple linear regression analysis. The results showed that PKB had a significant influence on PAD with a t-value of 1.390 and a significance level of 0.037, while BBNKB showed a very significant influence with a t-value of 3.859 and a significance level of 0.011. The F test showed that the overall regression model was significant in predicting PAD with an F value of 4.590 and a significance of 0.050. These findings affirm the importance of regional tax and levy management in increasing PAD, as well as providing input for the government in improving tax compliance and the effectiveness of regional resource management.